WE1.2: Gender Based Analysis Plus: A strengthened approach to gender integration and intersectionality - Morgan, Miranda (Bioversity International and the International Center for Tropical Agriculture, 2022)
The Government of Canada has been using Gender Based Analysis (GBA) as an analytical tool to support the development of more responsive and inclusive initiatives for over 25 years. The approach has changed over time, moving from ‘GBA' to ‘GBA Plus' to signify the range of identity factors beyond gender (such as age, race, religion, disability, socioeconomic status, geographical concerns, etc) that constitute inequality and need to be integrated in analyses to support more inclusive policies. An even more recent iteration of the GBA Plus approach emphasizes the role of social relations, structures and systems of oppression for producing and maintaining inequalities. Together these changes and the resulting tools are enabling researchers, analysts and policymakers alike to develop and engage with deeper and more intersectional social analyses. This session will introduce participants to the strengthened approach to GBA Plus, highlight useful and accessible GBA Plus guidance and tools, and identify ways the GBA Plus approach could support more intersectional and socially inclusive agri-food system research and policies. During the session there will be space to discuss the challenges and limitations of using a ‘gender-first' or additive approach to intersectionality and to highlight an example of how external partners (in this case, Canada's main Indigenous women's organisations) develop and use their own GBA Plus frameworks tailored to their respective contexts.